Pairing of α‐Fused BODIPY: Towards Panchromatic n‐Type Semiconducting Materials. Issue 26 (25th April 2019) - Huaulmé, Quentin; Fall, Sadiara; Lévêque, Patrick; Ulrich, Gilles; Leclerc, Nicolas
Abstract: A chemical strategy to efficiently perform the dimerization of α‐fused boron‐dipyrromethene (BODIPY) is reported. The straightforward synthesis of one of these dimers is described and its properties have been investigated through UV/Vis spectroscopy, cyclic voltammetry, differential scanning calorimetry, and charge‐carrier mobility measurements by using organic field‐effect transistors and space–charge‐limited current diodes. The results allow a chemical strategy to decrease the tendency of α‐fused BODIPY to crystallize, to increase its light‐harvesting properties, and to promote isotropic charge carriers transport. Moreover, the disclosed approach is also a way to maintain the deep LUMO level of α‐fused BODIPY; thus making this class of materials highly desirable for optoelectronic applications. Abstract : Counteracting crystallization : A chemical strategy to efficiently dimerize α‐fused boron‐dipyrromethene (BODIPY) is reported. This strategy is used to decrease the tendency of α‐fused BODIPY to crystallize, to increase its light‐harvesting properties (see figure), and to promote isotropic charge carriers transport.